Escola e escolares: a pandemia da Covid-19 pela perspectiva de educadoras e educadores da rede pública de Rio Claro – SP - Morais, Nattany Ribeiro de (Universidade Federal de São Carlos, 2024)
The COVID-19 pandemic has had extensive impacts on various spheres of society, including health, economy, education and daily routines. The education sector, in turn, faced significant challenges during the pandemic period, such as the total suspension of classes, the distancing of the population from the school environment for a long period, the lack of articulation from the Ministry of Education, the differences regional areas and scarce material and human resources, especially in the public sphere. Some studies indicated that during the period of social isolation, schoolchildren had impacts on their mental health, such as fear of contamination, frustration and irritability. Other dimensions verified, among the impacts generated by social isolation, included domestic violence, parents' difficulty in supervising their children and worsening social vulnerability. Teachers, who were already facing devaluing speeches on a daily basis, were also impacted in their personal and professional lives, and were thrown into a narrative that called on them to make profound changes in the way of being, thinking and conducting their teaching practices. National studies, although understandably carried out, for the most part, through devices connected to the internet, focused on aspects related to the possible impacts generated by the pandemic, with students as the main focus and, considering in particular, the period of greater social isolation. The results indicated the vulnerability to which both students and teachers would be exposed and highlighted the importance of continuing and deepening investigations throughout the pandemic context. The present study aimed to understand the socio-emotional conditions of public elementary school students and teachers throughout the pandemic, from the perspective of educators in a medium-sized municipality in the state of São Paulo. This is an exploratory study with a qualitative approach, which involved the participation of sixteen elementary school teachers from the public school system in a medium-sized municipality in the state of São Paulo. To collect data, a semi-structured interview guide was used that covered everything from different moments of the pandemic that had implications on the school routine to the resumption of in-person teaching. The interviews completed by the participants were transcribed and analyzed using the Collective Subject Discourse method. From the teachers' perspective, the results revealed the impacts of the pandemic on the daily lives of students and their families throughout the COVID-19 pandemic, highlighting the increase in some vulnerabilities such as, for example, unemployment, loss of loved ones dear greater exposure of children to situations of domestic violence, and also, losses in learning, delays in socio-emotional development, among others, were observed. The relevance of the place and the role of teachers and school in the lives of students was revealed beyond the aspects already widely known, with emphasis on the teachers' acute sensitivity and recognition of the students' reality; relationships of affection, care and attention; sharing and different demands entrusted by students and/or family members to teachers, among others. In relation to the teachers themselves and their experiences and challenges throughout the pandemic, the study revealed that the abrupt break in contact impacted the mental health of the interviewees by requiring them to adapt to new technologies and increasing work overload, resulting from the preparation of materials, and the requirement of support for students and families. Furthermore, teachers were the target of criticism, demands and, at times, unfairly blamed. The profound impact of the pandemic on the experiences of students and educators, emphasizing the protective role of the school, was highlighted. The need for support, training and effective strategies to deal with the complexities imposed by the pandemic in the educational context is discussed. The gap in listening to teachers was highlighted, highlighting the importance of listening to them in person at such a delicate time.
School and students: the Covid-19 pandemic from the perspective of educators from the public network of Rio Claro – SP
Keywords: Pandemia de COVID-19; Escola; Saúde mental infantil; Educadores; Estudantes; Terapia Ocupacional; CIENCIAS DA SAUDE::SAUDE COLETIVA::SAUDE PUBLICA